American Evangelicalism, by N. Magnuson and W. G. Travis & Twentieth-Century Evangelicalism, by E. L. Blumhofer and J. A. Carpenter - Guenther, Bruce L. (Arc: The Journal of the School of Religious Studies, 1993)
The author in this one submission offers a review of two different books, which seek to discuss evangelical Protestantism. 1. American Evangelicalism: An Annotated Bibliography. By Norris Magnuson and William G. Travis. West Cornwall, CT: Locust Hill Press, 1990. ISBN 0-933951-27-2. Pp. xix+495. 2. Twentieth-Century Evangelicalism: A Guide to the Sources. By Edith L. Blumhofer and Joel A. Carpenter. New York: Garland Publishing, Inc., 1990. ISBN 0-8240-3040-0. Pp. xv+384.